Strategi Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di Smp Nurul Huda Grujugan Kidul Bondowoso - Mohammad Bilutfikal Khofi (Universitas Darunnajah Jakarta, Indonesia, 2024)
Abstract This study examines the strategies employed by the principal of SMP Nurul Huda Grujugan Kidul Bondowoso in improving teacher performance. Teacher performance is critical in achieving quality education and reflects teachers' professionalism, skills, and dedication in executing their daily tasks. Effective school leadership plays a vital role in motivating teachers, providing necessary support, and creating an environment conducive to professional growth. This research aims to identify and analyze the strategies that have proven effective in enhancing teacher performance, focusing on areas such as competence development, discipline enforcement, motivation, and recognition. Using a qualitative descriptive approach, the study gathered data through interviews, observations, and document reviews involving school administrators and teachers. The findings reveal that regular training and workshops contributed to improving teaching skills, though some teachers faced challenges in integrating technology into their teaching practices. Discipline was reinforced through routine monitoring, clear leadership, and a structured reward and punishment system. Additionally, teacher motivation increased due to open communication, professional development opportunities, and balanced recognition systems. These strategies have positively impacted the overall teacher performance, contributing to a better educational environment at the school. The findings provide insights into effective leadership approaches that can enhance teacher motivation, discipline, and professional development.